Academic, social and economic experiences of first-year students: Case study - Bayaga, A.; Lekena, L. L.; Selepe, C.; du Plessis, A.; Blignaut, S.; Morar, T. (South African Journal of Higher Education, 2022)
The main precept of the current study was to explore first-year students’ academic, social and economic experiences at a University of Technology (pseudonym: University of Hard Knocks (UHK)). In response to the research questions, the study sought to interrogate the challenges faced by students by finding out whether they would choose the university again given a second chance, and if not why not. It also sought to establish how students would like the institution to improve in order to enhance first-year students’ experiences (FYSE). The approach applied was both quantitative and qualitative to allow students to reveal their experiences of the university, while simultaneously expressing such perceptions in descriptive format (for the quantitative part). Guided by Tinto’s (2013) student departure theory, data were collected using semi-structured questionnaires distributed and sent through invites to all 16 000 first (1st) year students – which served as the population. However, rested upon the research questions for the current study and given that the instrument used was semi-structured, data was received from participants totally 4020 for the quantitative aspect (mainly descriptive). Of this sample (4020), and for the purpose of the current research questions, forty (40) participants were further selected randomly, to evaluate their responses as directed and coordinated by the current research objectives. The results revealed that to ensure appropriate economic and social integration, efforts should be made to automate and secure university processes and, most importantly, provide accredited/licensed accommodation. To achieve effective academic integration systems, learning space and the lack of transparency in accommodation allocations should be addressed. It is therefore recommended that UHK considers economic, social and academic integration processes and procedures to improve the campus experience.